151 quick ideas to manage your time - Dittmer, Robert E., 1950- (151 quick ideas., 2018)
Do more in less time, take control of your schedule, and create a new balance between your work and your family life. You'll be surprised at how easy it is to take charge of your time and increase your quality of life-day by day, hour by hour, minute by minute.